(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the level of leadership management and the level of educational transformation practices of public elementary school heads. This study employed non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. One hundred twenty (120) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the level of leadership management was high while the level of educational transformation practices of public elementary school heads was also high. Moreover, the overall results disclosed that indicators for the leadership management had a strong positive correlation to the educational transformation practices of public elementary school heads. Further, results from the regression analysis revealed the following have a strong influence of leadership management on educational transformation practices of public elementary school heads: Democratic, Instructional, and Transformational Style. It is suggested that the Department of Education should conduct seminars and workshops on Different Leadership and Management Styles to sustain a high performance of school heads in managing and leading the school. It is also recommended that professional development training opportunities for school heads are needed to be addressed to attain basic education targets.